1999
DOI: 10.1021/ja991207z
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Effects on Intramolecular Quenching of Aromatic Ketone (π,π*) Triplets by Remote Phenolic Hydrogen Abstraction

Abstract: The photochemistry of a series of alkoxyacetophenone derivatives bearing remote phenolic groups has been studied using laser flash photolysis techniques. The compounds are structured with a p- or m-phenolic moiety attached via a m- or p-oxyethyl linkage to the carbonyl chromophore, and each have a lowest triplet state of π,π* configuration. The corresponding methoxy-substituted compounds have also been examined. The triplet lifetimes of the phenolic ketones vary with the positions of attachment (meta or para) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 73 publications
4
29
0
Order By: Relevance
“…Similar conclusions apparently also hold for the quenching of other triplet sensitizers like biacetyl [16] and flavin derivatives [17,18] by anisole, which prompted researchers to use anisole (derivatives) as low-reactivity reference systems for the chemistry of phenols. [19][20][21] While our own results for some BP derivatives are in accord with the charge-transfer mechanism in ACN solutions, we show herein that the reactivity of triplet excited BP towards anisole is dramatically dependent on the nature of the solvent. In particular, the reactivity of this system is dramatically enhanced in protic solvents and even reaches the reactivity of the well-documented BP/phenol system.…”
Section: Introductionsupporting
confidence: 77%
“…Similar conclusions apparently also hold for the quenching of other triplet sensitizers like biacetyl [16] and flavin derivatives [17,18] by anisole, which prompted researchers to use anisole (derivatives) as low-reactivity reference systems for the chemistry of phenols. [19][20][21] While our own results for some BP derivatives are in accord with the charge-transfer mechanism in ACN solutions, we show herein that the reactivity of triplet excited BP towards anisole is dramatically dependent on the nature of the solvent. In particular, the reactivity of this system is dramatically enhanced in protic solvents and even reaches the reactivity of the well-documented BP/phenol system.…”
Section: Introductionsupporting
confidence: 77%
“…A recent photochemical study of molecules linking phenol with aromatic ketones showed that the intramolecular hydrogen bond between phenol and the excited triplet ketone induced an electron transfer followed by proton transfer. 45 In this mechanism, the contribution of the tunneling effect should be negligibly small.…”
Section: Resultsmentioning
confidence: 99%
“…The implications of the presence of such light-absorbing organics and the possible photochemical reactions are not yet well understood in the sea surface microlayer. But clearly, the presence of such photoactive compounds at the air/sea interfaces could give rise to photosensitized processes (Becker et al, 1995;Canonica et al, 2006Canonica et al, , 2000Canonica et al, , 2005Das et al, 1981;Ivanov et al, 2005;Lathioor and Leigh, 2001;Lathioor et al, 1999;Leigh et al, 1996) which may also affect chemistry in the marine boundary layer (MBL) (Reeser et al, 2008). Previously, we showed that chlorophyll may be a photochemical source of halogenated radicals or the driving force for ozone deposition at low wind speed (Clifford et al, 2008).…”
Section: Introductionmentioning
confidence: 99%